2011
DOI: 10.1158/0008-5472.can-11-0532
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral De Novo Steroid Synthesis Activates Androgen Receptor in Castration-Resistant Prostate Cancer and Is Upregulated by Treatment with CYP17A1 Inhibitors

Abstract: Relapse of castration-resistant prostate cancer (CRPC) that occurs after androgen deprivation therapy of primary prostate cancer can be mediated by reactivation of the androgen receptor (AR). One important mechanism mediating this AR reactivation is intratumoral conversion of the weak adrenal androgens DHEA and androstenedione into the AR ligands testosterone and dihydrotestosterone (DHT). DHEA and androstenedione are synthesized by the adrenals through the sequential actions of the cytochrome P450 enzymes CYP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
377
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(394 citation statements)
references
References 38 publications
14
377
1
2
Order By: Relevance
“…The Physicians' Health Study confirmed the starting hypothesis, namely that testosterone and dihydrotestosterone (DHT) were positively associated with estradiol, and that sex hormone binding globulin was inversely associated with prostate cancer (Gann PH et al 1996). In recent years, several clinical studies of hormone treatment for prostate cancer have been done (Cai C et al 2011;Chang KH et al 2011;Mostaghel EA et al 2011;Richards J et al 2012;Mostaghel EA 2013). Prostate-specific antigen (PSA) is a glycoprotein produced almost exclusively by the epithelial cells of the prostate gland, and is used as a marker for the diagnosis and monitoring of prostate cancer (Hudson MA et al 1989;Oesterling JE 1991;Armbruster DA 1993).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The Physicians' Health Study confirmed the starting hypothesis, namely that testosterone and dihydrotestosterone (DHT) were positively associated with estradiol, and that sex hormone binding globulin was inversely associated with prostate cancer (Gann PH et al 1996). In recent years, several clinical studies of hormone treatment for prostate cancer have been done (Cai C et al 2011;Chang KH et al 2011;Mostaghel EA et al 2011;Richards J et al 2012;Mostaghel EA 2013). Prostate-specific antigen (PSA) is a glycoprotein produced almost exclusively by the epithelial cells of the prostate gland, and is used as a marker for the diagnosis and monitoring of prostate cancer (Hudson MA et al 1989;Oesterling JE 1991;Armbruster DA 1993).…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, DHEA (which is synthesized by the adrenal glands through the sequential actions of the cytochrome P450 enzymes CYP11A1 and CYP17A1) makes CYP17A1 inhibitors such as abiraterone effective therapy for castration-resistant prostate cancer (Cai C et al 2011). A recent study found an inverse correlation between serum levels of TCDD and testosterone in US veterans of the Vietnam War (Gupta A et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further details of instrument set up are included in Supplementary Methods for reference. Both the TSQ Vantage and 4000 QTRAP were operated in SRM mode to selectively measure the following AR peptides: GAFQNLFQSVR (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and LLDSVQPIAR (862-871). The unlabeled, "heavy" labeled ( 13 C 6 , 15 N 4 R, Ć¾10 Da), and "medium" labeled ( 13 C 6 , Ć¾6 Da) forms of both peptides were measured in parallel.…”
Section: Relative Peptide Quantification By Srmmentioning
confidence: 99%
“…However, although the activity of these agents in CRPC is very encouraging, neither works in all patients and both are associated with the development of additional resistance. Although the mechanisms by which tumors become refractory to abiraterone acetate and enzalutamide treatment have not yet been clearly elucidated, current clinical (4,25) and preclinical (26)(27)(28) data suggest that re-activation of the AR will remain a primary mechanism. Thus, there is a continued need to identify alternative therapies for the treatment of CRPC, and in particular those that have a mechanistically distinct inhibitory effect on AR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…To date, despite intensive speculation, there are only limited data available to suggest pathways that mediate resistance. Cai et al characterized abiraterone resistance in a murine model and found that the emergence of resistant VCaP cell lines was associated with an upregulation of the CYP17 enzyme [23]. Overcoming CYP17 upregulation could possibly be achieved with increasing doses of abiraterone or more potent CYP17 inhibitors, however this will incur greater mineralocorticoid side effects, and is likely to be temporary.…”
Section: Future Directionsmentioning
confidence: 99%